New calcium‐free Na2O–Al2O3–P2O5 bioactive glasses with potential applications in bone tissue engineering. Issue 2 (20th September 2017) - Jeznach, Oliwia; Gajc, Marcin; Korzeb, Karolina; Kłos, Andrzej; Orliński, Krzysztof; Stępień, Ryszard; Krok‐Borkowicz, Małgorzata; Rumian, Łucja; Pietryga, Krzysztof; Reczyńska, Katarzyna; Pamuła, Elżbieta; Pawlak, Dorota A.
Abstract: Sodium aluminophosphate glasses were evaluated for their bone repair ability. The glasses belonging to the system 45Na2 O– x Al2 O3 ‐(55‐ x )P2 O5, with x  = (3, 5, 7, 10 mol%) were prepared by a melt‐quenching method. We assessed the effect of Al2 O3 content on the properties of Na2 O–Al2 O3 –P2 O5 (NAP) glasses, which were characterized by density measurements, DSC analyses, solubility, bioactivity in simulated body fluid and cytocompatibility with MG‐63 cells. To the best of our knowledge, this is the first investigation of calcium‐free Na2 O–Al2 O3 –P2 O5 system glasses as bioactive materials for bone tissue engineering.